Enhancing Pharmaceutical Wastewater Treatment Through Adsorption With Rice Husk –derived Cellulose Nano Crystals as an Innovative Adsorbent (Journal of Environmental Bioremediation and Toxicology, 2024)
This study investigates the adsorption of the antibiotic metronidazole using cellulose nanocrystals (CNC) extracted from rice husk. The research highlights the importance of removing antibiotic contamination from water bodies and explores the potential of CNC as an adsorbent. The synthesis of CNC from rice husk achieved a yield of 26.46% through a series of pretreatment processes, including bleaching and acid hydrolysis. The CNC adsorbent was characterized using FTIR, BET, SEM, and XRD to determine its structural and surface properties, revealing a total pore volume of 0.225 cm³ and a micropore volume of 0.233 cm³. The effects of various parameters, including pH (with maximum adsorption at pH 9), temperature (optimal at 50°C), and time (maximum adsorption at 60 min), were also considered. The adsorption rate of metronidazole by CNC-RH increased with higher adsorbent dosage and adsorbate concentration. Adsorption kinetics were evaluated, with the pseudo-second-order model found to be the most appropriate. Adsorption isotherms were also studied, with the Freundlich model displaying excellent linearity (R² = 1). Thermodynamic parameters were calculated, including a negative ∆G (-103.566, -105.976, -110.796, -115.616, -120.46 J/mol), indicating a spontaneous process, a ∆S value of 0.482 J/molK, and a positive ∆H value of 40.07 J/mol, suggesting an endothermic process. Overall, this study offers valuable insights into the adsorption behavior of metronidazole using CNC derived from rice husk and underscores the importance of the selected parameters in the adsorption process.
Keywords: Cellulose nanocrystals (CNCs); Agricultural waste; Rice-husk; Adsorption efficiency; Metronidazole removal